Reconstruction of Online Gambling Sanctions in Indonesia: A Comparative Analysis of Ta'zir Sanctions and Penalties of the Electronic Information and Transaction Law - Harahap, Zul Anwar Ajim (Institut Agama Islam Negeri Curup, 2025)
The purpose of this study is to analyze and compare the effectiveness of sanctions under the ITE Law and jarimah ta'zir in addressing online gambling, and to explore how the integration of these approaches can create a more effective and comprehensive legal framework in Indonesia. This study employs a normative juridical method with an analytical approach to relevant laws and regulations, particularly the ITE Law and Qanun Jinayat in Aceh. Data were analyzed through a comparative evaluation of sanctions under the ITE Law and jarimah ta'zir, focusing on their effectiveness in tackling technological challenges, reducing recidivism, and creating social deterrence against online gambling. The findings reveal that the ITE Law, while effective in utilizing technological measures such as website blocking and account monitoring, faces limitations in providing a permanent deterrent due to the adaptability of gambling networks through VPNs, cryptocurrency, and domain migration. On the other hand, jarimah ta'zir, as implemented in Aceh, demonstrates significant success in reducing online gambling cases, with a recorded 35% decrease in cases in 2022, and a 10.53% decrease in overall criminal cases in Aceh Jaya in 2024 compared to 2023, primarily due to public punishments like caning, which create stronger social stigma and moral deterrence. Furthermore, the rehabilitative aspect of jarimah ta'zir offers a complementary approach to the punitive nature of the ITE Law, addressing the underlying causes of gambling behavior.